2015
DOI: 10.4067/s0718-34292015000300008
|View full text |Cite
|
Sign up to set email alerts
|

Physical seed treatment techniques may influence stand establishment and yield of wheat in delayed cropping

Abstract: Efectos de los tratamientos físicos en semillas de trigo sobre el establecimiento y producción del cultivoBahram Mirshekari 1 ABSTRACTGood crop establishment and its effect on productivity is one of the major challenges in crop production. To investigate the effect of seed priming by physical techniques on stand establishment and yield of delayed wheat sowing, two experiments were conducted in Tabriz, Iran. Wheat seeds were treated with ultrasound, laser, magnetic field, gamma and beta irradiation for 3.5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Seed priming is a pre-sowing seed treatment process that involves a regulated seed hydration step before radical emergence and this technique can induce rapid seed germination, stress tolerance, and synchronized seedling establishment (Bewley et al 2013 ; Paparella et al 2015 ). Among different seed priming methods, nutri-priming with inorganic fertilizers is considered to be quite advantageous in stimulating plant growth (Farooq et al 2007 ; Rehman et al 2011 ; Mirshekari, 2015 ). However, inorganic fertilizers (such as, Fe and Cu sulphate fertilizers)often contain a very high amount of heavy metals (like Cd, Cr, Pb, and Ni) which can be severely toxic for the environment and human health, and repeated use of these inorganic salts at such early stage of seedling development must be avoided (Gimeno-Gracia et al 1996 ; Otero et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seed priming is a pre-sowing seed treatment process that involves a regulated seed hydration step before radical emergence and this technique can induce rapid seed germination, stress tolerance, and synchronized seedling establishment (Bewley et al 2013 ; Paparella et al 2015 ). Among different seed priming methods, nutri-priming with inorganic fertilizers is considered to be quite advantageous in stimulating plant growth (Farooq et al 2007 ; Rehman et al 2011 ; Mirshekari, 2015 ). However, inorganic fertilizers (such as, Fe and Cu sulphate fertilizers)often contain a very high amount of heavy metals (like Cd, Cr, Pb, and Ni) which can be severely toxic for the environment and human health, and repeated use of these inorganic salts at such early stage of seedling development must be avoided (Gimeno-Gracia et al 1996 ; Otero et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, germinating red rice seeds significantly increased the seed content of GABA and riboflavin (vitamin B2) after ultrasound treatment 14 . Also, ultrasound treatment has been shown to increase chlorophyll content in wheat seedlings compared with seedlings that developed from untreated seeds 15 . Also, our lab found that tocochromanol and carotenoid content significantly increased in flax sprouts with dry ultrasonic pretreatment 16 .…”
Section: Introductionmentioning
confidence: 70%
“…14 Also, ultrasound treatment has been shown to increase chlorophyll content in wheat seedlings compared with seedlings that developed from untreated seeds. 15 Also, our lab found that tocochromanol and carotenoid content significantly increased in flax sprouts with dry ultrasonic pretreatment. 16 However, there are limited reports about the effect of wet ultrasonic pretreatment on phytochemicals in maize seedlings.…”
Section: Introductionmentioning
confidence: 83%
“…Magnetic field treatment can improve seed expansion and crop yield after germination without toxic residues compared to chemical methods. Relevant studies have shown that the application of the magnetic field with appropriate intensity to treat wheat seeds can improve the content of chlorophyll, nitrogen, phosphorus, and potassium in seedlings (Mirshekari, 2015). Shine et al (2012) found that magnetic field treatment could improve water absorption rate, germinating speed, seedling length, fresh weight, dry weight, and vigor index of soybean seeds.…”
Section: Introductionmentioning
confidence: 99%